Ethics in the Public Service in Africa: A Focus on the Nigerian Public Service - Davies, Emmanuel Opuene; Egbuchu, Sam Aleruchi (NIU Journal of Social Sciences, 2019)
A thorough observation of the Public Service in the African society, particularly in the past decades reveals a Public Service bedevilled with several unethical conduct and behaviour covering social, economic, religious and political dimensions. These unethical standards manifest in poor attitude to work, organisational irresponsibility, corruption, inefficiency, low level of productivity. The collapse of ethical and professional standards in the Public Service has led to crisis in governance, especially in the area of implementation of government policies and programs. The focus of this paper is on the examination of ethics in the Public Service in Africa with particular interest on Nigerian Public Service. Ethical standards have been ranked as one of the cardinal instruments of success of any organization. One of the major objectives of this study is to examine the character of administrative ethics in Nigeria and ultimately come up with useful suggestions on how to raise ethical standards which govern the performance of both the exercise of technical skills and operation of organizational procedures in the Public Service. Finally, this paper highlights recommendations geared at promoting ethical behaviour in Nigeria and Africa generally. Keywords: Ethics, Government, Public Service, Civil Service, Public organization, Society, Nigeria, Africa.